2016
DOI: 10.18632/oncotarget.7091
|View full text |Cite
|
Sign up to set email alerts
|

Nogo-B receptor promotes the chemoresistance of human hepatocellular carcinoma via the ubiquitination of p53 protein

Abstract: Nogo-B receptor (NgBR), a type I single transmembrane domain receptor is the specific receptor for Nogo-B. Our previous work demonstrated that NgBR is highly expressed in breast cancer cells, where it promotes epithelial mesenchymal transition (EMT), an important step in metastasis. Here, we show that both in vitro and in vivo increased expression of NgBR contributes to the increased chemoresistance of Bel7402/5FU cells, a stable 5-FU (5-Fluorouracil) resistant cell line related Bel7402 cells. NgBR knockdown a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(55 citation statements)
references
References 42 publications
0
55
0
Order By: Relevance
“…Some preliminary studies of NgBR expression in tumor cells have also been performed recently, but the results differ for different tumor types. For instance, NgBR was upregulated in breast cancer compared with normal breast tissue and the expression of NgBR promoted the chemoresistance of HCC cells (Dong et al, 2016;Wang et al, 2013). In contrast, association studies demonstrated that the expression of NgBR was negatively correlated with the malignancy grade in invasive ductal breast carcinoma, non-small-cell lung carcinomas, and malignant melanoma (Calik et al, 2016;Pula et al, 2014a,b).…”
Section: Discussionmentioning
confidence: 99%
“…Some preliminary studies of NgBR expression in tumor cells have also been performed recently, but the results differ for different tumor types. For instance, NgBR was upregulated in breast cancer compared with normal breast tissue and the expression of NgBR promoted the chemoresistance of HCC cells (Dong et al, 2016;Wang et al, 2013). In contrast, association studies demonstrated that the expression of NgBR was negatively correlated with the malignancy grade in invasive ductal breast carcinoma, non-small-cell lung carcinomas, and malignant melanoma (Calik et al, 2016;Pula et al, 2014a,b).…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, targeting this signalling axis has been revealed to be promising for the treatment of cancer. It has been predominantly reported to have an oncogenic function and elevated expression in certain cancer types, including invasive ductal breast carcinoma (IDC) (14), hepatocellular carcinoma (HCC) (15), malignant melanoma (MM) (16) and non-small cell lung carcinomas (NSCLC) (17), which implies that targeting this signalling axis may have potential for retarding or ameliorating cancer progression.…”
Section: Nogo-b Receptor In Relevant Carcinoma: Current Achievementsmentioning
confidence: 99%
“…In summary, NgBR serves a notable role in a number of human diseases, particularly cancer, which is a highly studied and complex subject (3). Once the first report of its effect on breast cancer was published in 2013 (14), numerous studies on the function of NgBR in the mechanism of cancer have been reported, and NgBR has gradually become a novel research hotspot globally (14)(15)(16)(17). However, no systematic review of the latest research results for NgBR in the cancer research field has been published, to the best of our knowledge.…”
Section: Nogo-b Receptor In Relevant Carcinoma: Current Achievementsmentioning
confidence: 99%
See 1 more Smart Citation
“…PI3K/AKT indirectly inhibits mTOR to cause cell cycle arrest and cell apoptosis (4). AKT activates MDM2 indirectly to decrease p53 level and activity, and promote p53 translation and protein stability (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%